PENAKSIR UNTUK RASIO POPULASI DENGAN MENGGUNAKAN TRANSFORMASI VARIABEL - Putri Rizqiyah; Harison '; Sigit Sugiarto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Estimators discussed in this paper are three estimators for population ratio using variable transformation, i.e estimator of population ratio using dual variable, regression-type estimator of population ratio, and ratio-type estimator of population ratio, which is a review from the article of Onyeka et.al [Global Journal of Science Frontier Research13(2013):57-65]. The three estimators are biased estimators. The most efficient estimator is the one that has the smallest mean square error obtained by comparing the mean square error of each estimator. An example is given at the end of the discussion.